HUBUNGAN ANTARA AGILITY DAN FUNCTIONAL PERFORMANCE PADA REMAJA DI SEKOLAH SEPAK BOLA SPARTA LIMO - Bayu Rizqi Ramadhan (2023)
Background: Agility is the ability of each individual to change direction agilely and efficiently without any disturbance of balance. Good agility can be seen if individuals can change the position of movement with high speed and neat coordination. Agility is one of the important aspects in soccer games, therefore the body condition of soccer players must always be in good condition, therefore the functional performance of each player must be in good condition too. Therefore, the author wants to analyze the relationship between agility and functional performance in adolescents at Sparta Limo soccer school. Design: The method used in this study is a correlational type. The sample needed in this study amounted to 32 people at Sparta Limo soccer school. The measuring instrument or parameter used to measure agility is the agility t-test while for functional performance a measuring instrument is used, namely the triple hoop test. Results: This study used SPSS 25 and obtained the results of p = 0.012 and r = 0.427 which means there is a relationship between agility and functional performance.Concludion: It is concluded that there is a relationship between agility and functional performance in adolescents at Sparta Limo soccer school.